2014
DOI: 10.1002/adma.201305539
|View full text |Cite
|
Sign up to set email alerts
|

AFM Imaging of Molecular Spin‐State Changes through Quantitative Thermomechanical Measurements

Abstract: Quantitative atomic force microscopy is used in conjunction with microwire heaters for high-resolution imaging of the Young's modulus changes across the spin-state transition. When going from the high spin to the low spin state, a significant stiffening is observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 35 publications
(57 reference statements)
1
23
0
Order By: Relevance
“…In the HS state, the average phase angle shift is very similar to that in the LS state (14.4° vs. 14.9°) at the same temperature. This result is somewhat surprising as the surface stiffness of the particles in the HS phase is expected to be significantly lower, which should be reflected by the phase images [20]. However, the cross-talk between the topography changes and the phase signal may hide the effect related to the variation of the sample visocoelastic properties [26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the HS state, the average phase angle shift is very similar to that in the LS state (14.4° vs. 14.9°) at the same temperature. This result is somewhat surprising as the surface stiffness of the particles in the HS phase is expected to be significantly lower, which should be reflected by the phase images [20]. However, the cross-talk between the topography changes and the phase signal may hide the effect related to the variation of the sample visocoelastic properties [26].…”
Section: Resultsmentioning
confidence: 99%
“…Up to now, mainly optical microscopy has been used for this aim in the SCO field (for examples see References [18,19] and references therein), but the limited spatial resolution of far-field optics makes this technique more suitable for the study of large single crystals several tenths of micrometers in size. In situ scanning probe microscopy [20,21,22,23,24] and electron microscopy [25] techniques have been only very recently employed on SCO materials, opening up exciting perspectives for the high spatial resolution analysis and manipulation of SCO objects in a broad size range. Here we present a variable-temperature AFM topography study of a nanocrystalline film of 1 with the aim to give a more comprehensive picture of the microstructural changes associated with the SCO in this sample.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23][24][25][26][27] Most reported complexes with hysteretic SCO are mononuclear or polymeric Fe II com-pounds, typically with neutral or cationic overall charge. Our group has focused in the search for anionic SCO complexes to increase their processing capabilities when incorporated into hybrid materials.…”
mentioning
confidence: 99%
“…In the case of thin SCO films, we have recently demonstrated that atomic force microscopy (AFM) force spectroscopy allows the spin transition to be probed with high spatial resolution . This approach is based on the ubiquitous decrease of the elastic modulus of SCO materials (by ≈10–50%) when going from the LS to the HS phase .…”
Section: Comparison Of Reported Elastic Moduli Ofmentioning
confidence: 99%